2022
DOI: 10.1021/acs.jafc.2c04101
|View full text |Cite
|
Sign up to set email alerts
|

Differential Protective Effect of Resveratrol and Its Microbial Metabolites on Intestinal Barrier Dysfunction is Mediated by the AMPK Pathway

Abstract: The effectiveness of resveratrol (RES) on intestinal barrier dysfunction and colitis has been extensively studied. However, the specific effects of its microbial metabolites on gut barrier function remain unclear. Hence, we compared the protective effects of RES and its microbial metabolites dihydroresveratrol (DHR) and 3-(4-hydroxyphenyl)-propionic acid (4HPP) against intestinal barrier injury and colitis. Only 4HPP and RES significantly reduced paracellular permeability and the secretion of proinflammatory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 67 publications
3
17
0
Order By: Relevance
“…Resveratrol is a well-known polyphenolic compound extracted at high levels from grape skins, peanuts, blueberries, and the roots of some CHMs, especially Polygonum cuspidatum , Morus alba L., and Panax notoginseng (Burkill) [ 101 , 102 ]. Due to its multiple anti-inflammatory, antioxidant, antitumor, and antimicrobial biological effects, resveratrol has been proven beneficial in various diseases, such as diabetes mellitus, obesity, cancer, and IBD [ 103 , 104 , 105 ]. The antimicrobial activity of resveratrol could impair the homeostasis of gut microbiota.…”
Section: Polyphenols Retard Oxidative Stress and Inflammation Via Mod...mentioning
confidence: 99%
“…Resveratrol is a well-known polyphenolic compound extracted at high levels from grape skins, peanuts, blueberries, and the roots of some CHMs, especially Polygonum cuspidatum , Morus alba L., and Panax notoginseng (Burkill) [ 101 , 102 ]. Due to its multiple anti-inflammatory, antioxidant, antitumor, and antimicrobial biological effects, resveratrol has been proven beneficial in various diseases, such as diabetes mellitus, obesity, cancer, and IBD [ 103 , 104 , 105 ]. The antimicrobial activity of resveratrol could impair the homeostasis of gut microbiota.…”
Section: Polyphenols Retard Oxidative Stress and Inflammation Via Mod...mentioning
confidence: 99%
“…The main evidence about the potential positive effects of resveratrol for the gut barrier is based on the in vitro studies, which were focused on the changes in the regulatory pathways. The most commonly used cell line was Caco-2 [ 82 , 83 , 84 , 85 ] and intestinal porcine enterocytes (IPEC-J2) [ 86 , 87 ]. The intestinal permeability in these studies was assessed by the measurement of transepithelial electrical resistance (TEER) across the cellular monolayer and by the measurement of the expression of the genes and corresponding proteins.…”
Section: Effect Of Resveratrol On the Gut Barriermentioning
confidence: 99%
“…A recent study evaluated the effect of resveratrol and its metabolites resulting from microbiota metabolism, namely dihydroresveratrol and 3-(4-hydroxyphenyl)-propionic acid on the intestinal barrier in LPS-treated Caco-2 cells [ 85 ]. It was found that only resveratrol and 3-(4-hydroxyphenyl)-propionic acid have beneficial effects on the intestinal barrier by increasing the expression of TJ protein and Muc2, and the molecular mechanism proposed by authors to be involved is monophosphate-activated protein kinase (AMPK)-mediated activation of CDX2 and the regulation of the SIRT1/NF-κβ pathway.…”
Section: Effect Of Resveratrol On the Gut Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…Pinosylvin (PS, 6 ) and dihydropinosylvin (DHP, 7 ) are RSV analogs found mainly in white pines, and DHP is the metabolite of PS by gut microbiota. , 4,4′-Dihydroxystilbene (DHS, 8 ) is a RSV analog found in Yucca periculosa . These RSV analogs and metabolites have many pharmacological activities, including antidiabetic, antitumor, antioxidative, and anti-inflammatory effects. ,, …”
Section: Introductionmentioning
confidence: 99%